PENGARUH PERSONAL SELLING, DISPLAY PRODUCT DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING - Didid Haris Bahtiyar Rizal (Universitas muhammadiyah malang, 2015)
This research aims to examine and analyze the effects of personal selling, product display, and store atmosphere simultaneously and partially towards consumer impulse buying consumer hypermart departemen store Malang Town Square. The sample size consisted of 100 respondents taken by accidental sampling. The data was analyzed by using the multiple linear regressions. The results showed personal selling, product display, and store atmosphere has the effect of simultaneously and partially towards impulse buying department store consumer matahari departemen store Malang Town Square. Variables store atmosphere dominant influence impulse buying in the consumer hypermart departemen store Malang Town Square.